Impact of culinary medicine elective on medical students’ culinary knowledge and skills - Jaroudi, Sarah S. (Proc (Bayl Univ Med Cent), 2018)
Diet has an important role in the treatment and prevention of chronic illnesses. Physicians are regarded as having proficient knowledge about nutrition, but most believe that they lack an understanding of clinical nutrition. In fall 2016, a group of medical students developed a culinary medicine elective for 20 students at Texas Tech University Health Sciences Center School of Medicine in Lubbock that included four didactic sessions and four interactive cooking labs that culminated in a final contest. The elective was meant to educate medical students about nutrition and dietary habits for their own benefit and that of their future patients. Surveys were administered to participants before and after the elective. Results showed a significant increase in confidence in overall culinary skill level, knowledge of ingredients, knowledge of cooking techniques, and ability to use kitchen supplies (P = 0.002, 0.002, 0.0004, and 0.003, respectively). The culinary medicine elective appears to be a valuable addition to the medical school curriculum.